Cat flea infestation, evolution and endosymbionts, and community awareness towards fleas and flea-borne diseases / Noor Azrizal Abdul Wahid - Noor Azrizal , Abdul Wahid (2021)
The cat flea Ctenocephalides felis is the cosmopolitan ectoparasite infesting cats. Occurrence of this flea on cats has led to several disease problems resulted from its ectoparasitic activity and associated pathogens. For prevention measure, study on its prevalence and genetic structure can help in identifying the infestation risk factors and its vectorial capability. In this study, infestation survey indicated overall high prevalence (71.8 %) of C. felis on cats sampled from four different regions in Peninsular Malaysia and the prevalence was associated (p < 0.05) with several risk factors including age, body weight, hair length, body condition and status of the cats. Among the regions, infestation rate was significantly highest on cat population in western region (28.9 %). Moreover, an assessment of knowledge, attitudes and practices (KAP) among cat owners showed possession of moderate level for knowledge on fleas and relatively low level for knowledge on flea-borne diseases. However, there were positive attitudes and good practices shown by the community in regard to prevention measures. Principle Component Analysis of KAP level, nevertheless, did not exert any variability among the respondents from different regions. Furthermore, analysis of cat flea mtDNA inferred from barcoding genes (cox1 and cox2) showed genetic variations between the four regions with western demonstrated the highest genetic diversity (Hd = 0.7833, Pi = 0.0127, Nh = 9). However, in overall, this study observed low nucleotide and haplotype diversities, indicating high homogeneity in genetic content among flea populations resulted from high gene flow. There were 15 haplotype numbers (AB1 – AB15) revealed in cat flea populations in Malaysia. Global comparison, however, indicated that Malaysian cat fleas had limited geographical distribution within Southeast Asian region while had genetic proximity with population from tropical region. Analyses of endosymbiont bacteria showed that cat fleas in Peninsular Malaysia carry Bartonella and Rickettsia bacteria with 28 % of flea samples were positive for Bartonella DNA and 14 % for Rickettsia DNA. Meanwhile, the tested flea populations were negative for Mycoplasma infection. Three Bartonella species were recorded including B. clarridgeiae, B. hensalae and the first record in Malaysia, B. koehlerae. Meanwhile, Rickettsia asembonensis was the only rickettsial bacteria identified in the present study. Statistical analyses revealed no association on the bacterial infection towards the mtDNA diversity of the cat fleas. However, in overall pathogen infection, infected population demonstrated lower haplotype and nucleotide diversities and showed lower number of haplotypes. Ultimately, the finding from this study will be beneficial in flea management and control program related to veterinary practices by providing insights on flea infestation, community awareness, evolution and its associated pathogens. The present findings highlighted the need for ongoing public health programs, given the relatively low possession of flea related knowledge among cat owners, and high infection rates of pathogens in cat flea populations in Peninsular Malaysia.